Analysis of The Character Value Relevance Analysis of Theme 4 "Obligations and Rights" in The Character Forming of Class III Students in Elementary School : Analisis Relevansi Muatan Nilai-Nilai Karakter Tema 4 "Kewajiban dan Hakku" dalam Pembentukan Karakter Siswa Kelas III Sekolah Dasar - Nurdiana Faizah Andriani; Supriyadi Supriyadi (Academia Open, 2021)
This study discusses the analysis of the relevance of the content of character values ​​in theme 4 "Duties and Rights" in the formation of the character of third grade elementary school students. With this, the researchers found problems that need to be researched. The problem is about how the character values ​​are loaded in the thematic book for students in theme 4 "Duties and Rights" for grade III elementary school. This research is a qualitative research using content analysis method. The data subject is the student book theme 4 "Duties and Rights" revised edition 2018. The character values ​​that are the focus of this research are the value of self-confidence, the value of disciplined character, the value of the character of responsibility, the value of caring character, and the value of polite character. The results obtained from this study are the five characters in accordance with the Regulation of the Minister of Education and Culture No. 64 of 2013 concerning Content Standards for Primary and Secondary Education. The frequency of occurrence of character values ​​analyzed is 57 which consists of 10 occurrences of confident character, 5 frequency of appearance of discipline character, 12 frequency of appearance of responsibility character, 16 frequency of appearance of caring character, and 14 frequency of appearance of polite character.